2008
DOI: 10.1182/blood-2007-11-126003
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of agents that eradicate leukemia stem cells using an in silico screen of public gene expression data

Abstract: Increasing evidence indicates that malignant stem cells are important for the pathogenesis of acute myelogenous leukemia (AML) and represent a reservoir of cells that drive the development of AML and relapse. Therefore, new treatment regimens are necessary to prevent relapse and improve therapeutic outcomes. Previous studies have shown that the sesquiterpene lactone, parthenolide (PTL), ablates bulk, progenitor, and stem AML cells while causing no appreciable toxicity to normal hematopoietic cells.Thus, PTL mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(156 citation statements)
references
References 52 publications
4
152
0
Order By: Relevance
“…To test this strategy, we focused our efforts on the TF nuclear factor (NF)-kB, in part, because our promoter analysis revealed a significant enrichment of binding sites for NF-kB among genes dysregulated in APL, and in part, because NF-kB can be inhibited effectively by terpenoids such as Parthenolide. 32,38 Significantly, incubation of NB4 cells for 48 h with micromolar concentrations of Parthenolide resulted in a substantial inhibition of proliferation and induction of apoptosis ( Figure 5). The latter suggests that comprehensive promoter analysis of dysregulated genes in APL can identify TFs, which at least to some extent, might represent potential targets for therapeutic interventions.…”
Section: Validation Of Candidate Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this strategy, we focused our efforts on the TF nuclear factor (NF)-kB, in part, because our promoter analysis revealed a significant enrichment of binding sites for NF-kB among genes dysregulated in APL, and in part, because NF-kB can be inhibited effectively by terpenoids such as Parthenolide. 32,38 Significantly, incubation of NB4 cells for 48 h with micromolar concentrations of Parthenolide resulted in a substantial inhibition of proliferation and induction of apoptosis ( Figure 5). The latter suggests that comprehensive promoter analysis of dysregulated genes in APL can identify TFs, which at least to some extent, might represent potential targets for therapeutic interventions.…”
Section: Validation Of Candidate Drugsmentioning
confidence: 99%
“…25,26 In contrast, genes upregulated in APL cells versus PMs contained a significant enrichment of binding sites for TFs that are instrumental for malignant transformation in cell lines and AML (MZF1, ARNT), and most strikingly for proliferation, mobilization and self-renewal of HSCs and/or leukemic stem cells (LSCs) (ERG1, NFKB, NFKB1). [27][28][29][30][31][32] APL cells show a partial stemness signature Our promoter analysis revealed that genes upregulated in APL cells versus PMs were significantly enriched in binding sites for TFs that conduct HSC maintenance/self-renewal. This led us to the hypothesis that APL cells might differ form PMs by expression of genes associated with HSC maintenance/selfrenewal.…”
Section: Transcriptional Regime Of Genes Dysregulated In Aplmentioning
confidence: 99%
“…This database can be queried with any gene-expression profile of interest (e.g., the expression profile of a compound, or a disease) and the results yield a list of the CMap drugs ranked, according to the similarity with the signature of interest. Hence, drugs with negative score (opposite profiles) might have the potential as new treatments for specific diseases, [12][13][14] while drugs with positive score (similar profiles) could be useful for identification of novel actions of existing drugs 15 or to unravel drug mechanisms of action. [16][17][18] Using the gene expression profile produced by the antiinflammatory pro-resolving molecule annexin A1 (AnxA1), 19 we found very strong positive connections with several members of the histone deacetylase inhibitors (HDACIs) class of drugs.…”
mentioning
confidence: 99%
“…It is important to emphasize that natural compounds have also been reported to target TICs selectively, with parthenolide (PTL) being the first such compound described (Guzman et al, 2005(Guzman et al, , 2007Steele et al, 2006;Hassane et al, 2008;Kawasaki et al, 2009). PTL is a sesquiterpene lactone found in feverfew (Chrysanthemum parthenium), which has been traditionally used to treat migraine and rheumatoid arthritis and exerts activity as nuclear factor-kB inhibitor, p53 activator (via ubiquitination of MDM2, mouse double minute 2-p53 binding protein homolog), DNMT1 (DNA (cytosine-5-)-methyltransferase 1) inhibitor and promoter of HDAC1 depletion by proteosome degradation (Gopal et al, 2007).…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%
“…PTL is a sesquiterpene lactone found in feverfew (Chrysanthemum parthenium), which has been traditionally used to treat migraine and rheumatoid arthritis and exerts activity as nuclear factor-kB inhibitor, p53 activator (via ubiquitination of MDM2, mouse double minute 2-p53 binding protein homolog), DNMT1 (DNA (cytosine-5-)-methyltransferase 1) inhibitor and promoter of HDAC1 depletion by proteosome degradation (Gopal et al, 2007). Using the global transcription response to PTL, a collection of compounds that mimic the effect of PTL were discovered and shown to target acute myeloid leukemia stem cells (Hassane et al, 2008). Two of these, celastrol (a terpenoid) and 4-hydroxynonenal (a nonterpenoid lipid peroxidation product) are also natural products, whereas one additional hit, 15-deoxy-D12,14-PGJ2, is a prostaglandin derivative.…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%